2004
DOI: 10.1155/2004/483591
|View full text |Cite
|
Sign up to set email alerts
|

Cell apoptosis specific marker found by Fourier Transform Infrared Spectroscopy

Abstract: We used Fourier Transform Infrared Spectroscopy (FTIR) combined with flow cytometry to study the apoptosis and necrosis processes in Jurkat, a lymphocyte cell line. The apoptosis was induced in the cells by a chemical agent, the actinomycin D, while the necrosis was induced lowering the pH value to 4.2. The apoptotic events were analysed by flow cytometry (using annexin V and propidium iodide) and contemporary monitored by FTIR spectroscopy at different times after the treatment. This comparison allowed us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 12 publications
3
35
0
Order By: Relevance
“…2, there was a dramatic increase in this region whose spectrum is populated by absorptions stemming from the C-H stretching vibrations of olefinic =CH, -CH 2 and −CH 3 groups [18,19,23,25]. Band assignment (see [20][21][22][23][24][25][26][27][28][29]). As illustrated in Fig.…”
Section: The Absorption Band Region At 3600-2800 CM −1mentioning
confidence: 99%
“…2, there was a dramatic increase in this region whose spectrum is populated by absorptions stemming from the C-H stretching vibrations of olefinic =CH, -CH 2 and −CH 3 groups [18,19,23,25]. Band assignment (see [20][21][22][23][24][25][26][27][28][29]). As illustrated in Fig.…”
Section: The Absorption Band Region At 3600-2800 CM −1mentioning
confidence: 99%
“…At present Fourier Transform Infrared Microspectrosopy (FTIRM) and Confocal Raman Microspectroscopy (CRM) have identified in-situ molecular alterations associated with cell death via apoptosis [1][2][3] or necrosis [4,5], or as a result of proliferative changes in cellular activity [6][7][8] or mitosis [9]. It has also been shown that these modalities can identify molecular changes associated with changes in the phenotype of differentiating embryonic cells [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Gaudenzi et al (2004) found a positive correlation between the vibrational band of ~2928 cm -1 increasing in intensity and the detection of the % apoptosis using annexin-V. Annexin-V binds to phosphatidylserine, which is a phospholipid externalized during apoptosis. It was speculated by Gaudenzi et al (2004) that the vibrational band could be directly attributed to phosphatidylserine (Gaudenzi et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…FTIR-and Raman spectroscopy have demonstrated biomedical applications in cancer research (Diem et al, 2012;Mantsch et al, 2002) including the ability to differentiate between healthy and cancerous cells / tissues, spectral differences between different tissues and types of cancers, grading of the stage of cancer progression and drug discovery where new drug leads were tested against the proliferation of cancerous cells as well as investigations on the molecular mechanism of action of known chemotherapeutics. Some spectral regions have been identified where cell death induction led to spectral differences in FTIR data (Gaudenzi et al, 2004;Holman et al, 2000;Jamin et al, 2003;Munro et al, 2010;Notingher et al, 2003). In this investigation, we set out to determine whether FTIR microspectroscopy could successfully distinguish between viable, apoptotic and necrotic cells.…”
Section: Introductionmentioning
confidence: 99%